Context-based service for intelligent public transportation systems. (2015) - Stanciu, Valeriu-Daniel; Dobre, Ciprian; Cristea, Valentin
Nowadays, cities become ever more populated, starting to represent an enormous source of pollution, congestion and overcrowding. Technology is evolving at a very fast speed; most of the people have a smartphone and are using it on a daily basis. In this paper, we describe a service designed to assist citizens take informed decisions regarding the means of transportation, to make them more aware of public transportation alternatives. We propose techniques to deal with mobility of people (monitor individual and group travelling conditions), and propose alternative means of transportation considering the active use of context information. The idea is to use the mobile apps capable of understanding the user's environment and reacting accordingly.